Study of genetic diversity in sunflower promising inbred lines using morphological traits - Avin, F.A.; Nabipour, A.; Zali, A. (2008)
One of the most important factors in breeding programs advancement is the evaluation and quantification of genetic diversity in breeding population. In the preparation of pre-breeding population and hybrid production, selection of convenient parents that are efficiently distant, is so important. In order to precise description for the sunflower genetic stocks of the Oilseed Department (Seed and Plant Improvement Institute, Karaj, Iran), morphological traits and oil percentage of 49 promising inbred lines including 18 R-lines and 31 B-lines were studied using sunflower descriptor. These lines were planted based on a simple Lattice (7 x 7) design with 2 checks in 2005. Results of ANOVA revealed significant differences between the lines for almost all traits. Relationships between quantitative and quantitative traits, qualitative and quantitative traits and qualitative and qualitative traits were calculated, using correlation analysis, ANOVA and chi square method, respectively. Results showed that there is a negative correlation between oil percentage and 100 seed weight. Classification of lines based on cluster analysis grouped the lines in to two distinct male and female groups. Factor analysis, extracted 4 factors that altogether comprised 73.92% of total variation in data. Biplot analysis based on the first two principle components clearly separated male and female lines. According to these findings Heterotic plausible groups were suggested for future crosses and hybrid assessment.